USING OF ADSORPTIVE AND CATALYTIC METHOD FOR CLEANING OF EMISSION INTO ATMOSPHERE WHICH ARE FORMED AT USING THE NON-STICK COVERINGS CONTAINING ETHYL ALCOHOL - A. S. Panasyugin; V. A. Lomonosov; O. L. Smorygo (Литьë и металлургия)
The article is dedicated to actual problem and is of scientific and practical interest. Purpose of this work is studying of process of the ethanol vapors neutralization by adsorption-catalytic method.